Comic strips as learning media in high school art education: A qualitative study - Diaspita; Nasution, Ikhwanuddin; Sebayang, Vanesia Amelia; Saragih, Erikson; Priyatno, Agus (Talenta Publisher, 2026)
This study examines the use of comic strips as a learning medium in high school fine arts education. It aims to explore how comic strips facilitate students’ understanding of artistic concepts, enhance motivation to learn, and shape classroom interactions. A descriptive qualitative approach was employed, involving classroom observations, semi-structured interviews, and documentation. The participants consisted of a fine arts teacher and students from grades XI-1 and XI-2 at SMAN 4 Medan. The findings indicate that comic strips effectively support the learning process by bridging abstract art concepts with practical application. Students demonstrated increased intrinsic motivation, as reflected in their active engagement, creative exploration, and sense of ownership over their work. In addition, comic-based activities improved students’ understanding of visual elements such as composition, perspective, and expression. The use of comic strips also fostered a more collaborative and dialogic classroom environment, encouraging peer interaction and discussion. Despite challenges such as limited time, varying drawing abilities, and initial difficulties in developing story ideas, the medium proved adaptable and inclusive for diverse learners. These findings suggest that integrating comic strips into fine arts curricula offers a relevant and innovative pedagogical strategy. It supports the development of visual literacy, creativity, and student-centered learning, particularly in addressing the needs of contemporary learners in visually oriented educational contexts.